An Experimental Study of Phytoremediation of Methyl-tert-butyl Ether (MTBE) in Groundwater - Q. Zhang; L. C. Davis; L. E. Erickson (Journal of Hazardous Substance Research, 1999)
The feasibility of phytoremediation of groundwater contamination with methyl-tert-butyl ether (MTBE) was examined experimentally using a six-channel soil system with or without plants. Two bacterial strains capable of degrading MTBE were each added to two out of six channels. A solution of 0.84 mM MTBE was continuously fed into each channel at 1 L/day until a stable MTBE concentration level in the groundwater was established; then the feeding was switched back to distilled water. The channel groundwater effluent MTBE concentration and the soil gas MTBE fluxes were monitored from the beginning of the MTBE solution feeding until no MTBE was detected. Integration of the gas flux data indicated that the four vegetated channels with introduced bacteria had less MTBE at the soil surface than channel 3 which was vegetated but without any introduced bacteria. The total mass balance for MTBE showed that the fractions of MTBE that were not recovered in the planted channels were significantly higher than in the unplanted channel. Analysis of the experimental data indicates that, due to the presence of the plants, MTBE might have been undergoing enhanced rhizosphere biodegradation.
Keywords: phytoremediation; MTBE; biodegradation; mass balance